Aspectos da narrativa transmídia como estratégia comunicacional no telejornalismo da TV Correio - Trindade, Mayara Praxedes Medeiros da (2022)
This dissertation aims to analyze aspects of transmedia narrative (and if these aspects exist because they were designed for this purpose, still in the production stage) present in the journalistic content of TV Correio, an affiliate of RecordTV in the state of Paraíba, characterized by distributed information in different media, going beyond the content broadcast on the station's traditional programming grid. To this end, literature reviews were carried out on the processes of transmediation and the specificities of transmedia narrative in contemporary television and television journalism, comparing and linking them with the communication strategies used by Correio. In this research, we assume that the transmedia narrative represents all the stories told through multiple media, arousing the interest of an audience willing to follow the unfolding of information through different platforms, monitoring the unfolding of a story, migrating between media and thus consuming your favorite format. As empirical objects of research, six editions of each of the main television news programs shown by the broadcaster, for the entire state, are cut out. Therefore, part of the methodological instruments included the monitoring, observation and analysis of television news, namely Correio Manhã, Correio Verdade, Cidade Alerta Paraíba and Jornal da Correio, as well as the station's Instagram, website and Youtube, pointing out the transmedia extensions identified during the observational stage. The analysis itself was carried out around two axes: a) the analysis of the narrative undertaken intentionally, in order to identify communicational aspects that can function as transmedia or that resemble the main objective of the format, which is to tell a only history through different media; b) the unconscious attempt to migrate audiences between different media, with unconsciousness being a reality not characterized as a transmedia narrative. The results obtained indicate that the aspects of transmedia narrative identified in TV Correio's telejournalism are, for the most part, developed unconsciously, that is, they are produced with the intention of migrating content and audiences between different platforms but, in their entirety, not “guide” this audience at all stages, an essential characteristic for a narrative to be identified as transmedia. This is due to the fact that the producers of media content that are part of the corpus of this analysis find, during the development of the information to be distributed, operational limitations that prevent them from knowing in depth the target audience of the product itself. Therefore, the narrative organization does not complement each other, since there is no active participation of the public in all the layers that make up a transmedia narrative, within the concept worked here.